2017
DOI: 10.1021/acs.langmuir.7b02576
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Induced Chirality: Twist and Stacking Handedness of the Biphenylene Groups of n-C12H25O-BP-CO-Ala-Ala Dipeptides

Abstract: In mixtures of water and dimethyl sulfoxide, 4'-(n-dodecyloxy)-1,1'-biphenyl-4-carbonyl Ala-Ala dipeptides can self-assemble into tubular structures that are formed by coiled nanoribbons. The twist and stacking handedness of biphenylene groups were studied using circular dichroism and confirmed by theoretical chemical calculations. The handedness of the coiled nanoribbons and the stacking handedness of biphenylene groups are controlled by the chirality of alanine at the C-terminus, whereas the twist handedness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
2
7
1
Order By: Relevance
“…The FE‐SEM images indicate that the handedness of the self‐assemblies is controlled by the chirality of the alanine near the alkyl chain. Such observation of handedness is quite similar to the previous report …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The FE‐SEM images indicate that the handedness of the self‐assemblies is controlled by the chirality of the alanine near the alkyl chain. Such observation of handedness is quite similar to the previous report …”
Section: Resultssupporting
confidence: 92%
“…In the field‐emission scanning electron microscopy (FE‐SEM) images (Figure ), all of the four dipeptide derivatives 4 could self‐assemble into twisted nanoribbons in methanol. Unlike the compounds with linkage of a biphenyl group and alanine dipeptides in our previous studies, no nano‐ or micro‐tubes was observed. The handedness of nanoribbons for (L, L)‐ 4 and (L, D)‐ 4 is left (Figure , a and b), while that of nanoribbons for (D, L)‐ 4 and (D, D)‐ 4 is right (Figure , c and d).…”
Section: Resultscontrasting
confidence: 91%
See 2 more Smart Citations
“…The above SEM results clearly indicated that the supramolecular chirality was solely determined by the chirality of the amino acid adjacent to the benzene core, irrespective of the absolute configuration of the terminal amino acid. This finding was contradictory to some previous reports that the supramolecular chirality was dictated by the C‐terminal chirality, which was called “C‐terminal rule.” [46–48] In fact, the gelators in those systems were amphiphilic molecules and upon self‐assembly the C‐terminal hydrophilic head group residues were located on the surface of the self‐assembled aggregates. It could be anticipated that terminal noncovalent interactions among gelators or solvents play a profound effect on controlling the supramolecular morphology and handedness [16] .…”
Section: Resultsmentioning
confidence: 99%